Upaya Meminimalisir Penyebab Kecelakaan Kerja Saat Bongkar Muat Di MV Ryoko 8 - Frinandi Magelhaens May, Frinandi; Wahju Wibowo; Aliong Silalahi (KALAO'S MARITIME JOURNAL, 2022)
The purpose of writing this scientific paper is to see what are the causes of work accidents when loading and unloading on the ship, in order to overcome this happening in order to prevent accidents on board. The research methods used in writing this scientific paper are three methods, namely the survey method, the interview method and the literature study method. The study was conducted on board the MV. Ryoko 8 with GT 4194, under the auspices of PT. The Andalas Bhatera Baruna / ABB. The results obtained from this study are several al that are the causes of work accidents on board ships, namely unsafe actions from humans and unsafe conditions. To prevent work accidents on board the ship, it is necessary to work with great care and also a sense of responsibility, prevent unsafe working conditions, and immediately report all incidents, irregularities, and damage to the slightest equipment to their superiors.